Document Purchase:Simplification of Procedure:A Case Study (Paper J) - Rahman, Abdul (Journal of Information and Knowledge, 1964)
Outlines the objectives of document procurement and stales the factors contributing to the delay in procurement of documents. Explains the procurement system for documents in a library belonging to an industry. Shows how a systematic study could be made of the existing procurement procedure to convince the management about the need for its simplification. Gives a model of a report prepared, incorporating such a study with necessary flow charts and notes. Concludes giving a flow chart of a procedure agreed upon as a result of the appreciation of the problem in a certain case.